Socio-demographic changes in north of Cauca and south of Valle between 1993 and 2005 censuses and the Páez Law - Urrea Giraldo, Fernando (Cuadernos de Administración, 2010)
This paper refers to the socio-demographic analysis of the region northern of Cauca and southern of Valle del Cauca (Colombia), via the ethnic-racial variable, using the censuses of 1993 and 2005 as the basic sources of statistical reference. Other statistical sources included are specific studies that have been made in the sub-region of the north of Cauca, plus an ethnographic study related to the Paez Law (Urrea y Hurtado, 1997; Escobar, 2003; Alonso y Lotero, 2006; Bermudez et al., 2007; DANE regional accounts between 1990-2005). The document begins with an introduction in which a social demographic and economic approach to the region takes place, emphasizing the largest demographic weight of black and indigenous peoples that live there. The paper continues with an analysis of the main socio-demographic tendencies in the inter-census period 1993-2005 for the 27 municipalities of the region, grouping them in three phases of demographic transition. The final part approaches to the socioeconomic context of the metropolitan area of Cali versus to Popayan and the Paez Law, to determine the interactions with the socio-demographic transformations observed in the municipalities of south of Valle del Cauca and north of Cauca.